Science Learning Management to Improve Student Learning Outcomes - Komara Nur Ikhsan; Rianti Cahyani; Waska Warta (International Journal of Nusantara Islam, 2021)
To improve learning outcomes in educational institutions, it is necessary to apply learning management, which is part of education management. Because educational management is a set of interrelated processes in achieving the goals of an educational institution. Based on the management theory of preliminary studies to improve student learning outcomes, educational institutions must apply the concept of learning management to educational institutions. This research will be carried out at MTS N 16 Ciamis, MTs Alhuda Sadananya, Ciamis Regency and MTs S Mujahidin, Tasikmalaya Regency on science learning management in an effort to improve learning outcomes. Natural Science learning management as an effort to improve student learning outcomes in Madrasah Tsanawiyah Negeri 16 Ciamis Regency, Madrasah Tsanawiyah Alhuda Sadanaya Ciamis Regency and Madrasah Tsanawiyah Mujahidin Sukaratu, Tasikmalaya Regency. Implement natural science learning management through management stages, namely science learning planning, organizing, implementing, as well as monitoring and evaluation.